Nonlinear pedagogy in skill acquisition an introduction - Chow, Jia Yi; Davids, K. (Keith) 1953-; Button, Chris 1973-; Renshaw, Ian (Routledge, 2016)
"Nonlinear pedagogy is a powerful paradigm for understanding human movement and for designing effective teaching, coaching and training programs in sport, exercise and physical education. It addresses the inherent complexity in the learning of movement skills, viewing the learner, the learning environment and the teacher or coach as a complex interacting system, with the constraints of individual practice tasks providing the platform for functional movement behaviours to emerge. This is the first book to explain this profoundly important new approach to skill acquisition, introducing key theoretical ideas and best practice for students, teachers and coaches. The first section of the book offers a general theoretical framework to explain processes of skill acquisition and the learning of movement skills. The book then defines nonlinear pedagogy, and outlines its key principles of practice. It offers a thorough and critical appraisal of the optimal use of instructional constraints and practice design, and discusses methods for creating challenging and supportive individualised learning environments at developmental, sub-elite and elite levels of performance. Every chapter contains cases and examples from sport and exercise contexts, providing guidance on practice activities and lessons. Nonlinear Pedagogy in Skill Acquisition is an essential companion for any degree level course in skill acquisition, motor learning, sport science, sport pedagogy, sports coaching practice, or pedagogy or curriculum design in physical education"--EBL